INCORPORATING CALLING INTO CAREER COUNSELING: HOW AND FOR WHOM? - Duffy, Ryan D.; Dik, Bryan J.; Blustein, Carly (Career Planning & Adult Development Journal)
The present manuscript summarizes the extant literature related to work being viewed as a calling and offers suggestions for incorporating calling into career counseling practice. Given the consistent relation of a calling with positive work and well being outcomes, we propose that career counselors be open to working with clients in finding the career they are called to do. This includes assessing the presence of a calling, exploring the process by which client's came to understand their calling, and helping clients match their calling with specific occupations. Additionally, we discuss how a client's unique life situation may relate to their experience of a calling.